Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s11145-006-9008-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the reading–writing connection in Chinese children with dyslexia in Hong Kong

Abstract: Comparing the analyses based on the data of 1,235 Chinese children referred for government services and subsequently diagnosed as children with dyslexia in Hong Kong and those of 690 Chinese children in the sample for the normative study of the Hong Kong Test of Specific Learning Difficulties in Reading and Writing, we explored the reading-writing connection through a series of regression and correlation analyses. Specifically, orthographic knowledge, naming speed, and phonological memory were found to be sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
78
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 24 publications
15
78
2
2
Order By: Relevance
“…Nevertheless, the research on reading and writing association in Chinese is not as systematic and extensive as that in English. Some researchers studied reading-to-writing relationship (Leong, Loh, Ki, & Tse, 2011;Lin et al, 2010;Qu, Damian, Zhang, & Zhu, 2011), whereas others studied writing-to-reading relationship (Chan, Ho, Tsang, Lee, & Chung, 2006;Guan et al, 2011, Guan, Ye, Wagner, & Meng, 2012, Guan, Ye, Meng, & Leong, 2013, Guan, Ye, Wagner, Leong, & Meng, 2014McBride-Chang et al, 2011Tan, Spinks, Eden, Perfetti, & Siok, 2005).…”
Section: Associations Between Reading and Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the research on reading and writing association in Chinese is not as systematic and extensive as that in English. Some researchers studied reading-to-writing relationship (Leong, Loh, Ki, & Tse, 2011;Lin et al, 2010;Qu, Damian, Zhang, & Zhu, 2011), whereas others studied writing-to-reading relationship (Chan, Ho, Tsang, Lee, & Chung, 2006;Guan et al, 2011, Guan, Ye, Wagner, & Meng, 2012, Guan, Ye, Meng, & Leong, 2013, Guan, Ye, Wagner, Leong, & Meng, 2014McBride-Chang et al, 2011Tan, Spinks, Eden, Perfetti, & Siok, 2005).…”
Section: Associations Between Reading and Writingmentioning
confidence: 99%
“…Once the motor memory has been learned and stabilized, it can last for long periods, and behavioral studies indicate that sensorymotor memory traces, inferable from stroke sequences in partial character primes, facilitate character recognition (Flores d'Arcais, 1994). Writing-reading connections were demonstrated in correlational studies with normal and dyslexic (Chan et al, 2006) Chinese children, and functional brain-imaging has shown that judging visual words involves brain areas possibly associated with writing (Siok, Niu, Jin, Perfetti, & Tan, 2008). Taken together, accumulating behavioral and neuroimaging research supports the hypothesis that writing experience contributes to reading skill in Chinese L1 literacy Siok et al, 2008).…”
Section: Associations Between Reading and Writingmentioning
confidence: 99%
“…The retrieved graphemes are then temporarily stored in the graphemic buffer (Rapp & Caramazza, 1997) of the working memory system before these graphemes are executed manually in the process of handwriting. On the basis of these models, it was hypothesized that among Chinese children CHINESE WRITING IN DYSLEXIC 7 with dyslexia, their degree of difficulties in performing Chinese word dictation would be associated with their deficits in lexical and orthographic knowledge (Ho et al, 2004;, as well as their lower efficiency in mapping the orthographic codes to psycho-motor codes of the Chinese characters (Chan, Ho, Tsang, Lee, & Chung, 2006;Tan, Spinks, Eden, Perfetti, & Siok, 2005). Moreover, as the previous studies consistently reported that the RAN deficit was the predominant deficit in Chinese children with dyslexia (e.g., Ho et al, 2004;, it was expected that this study would produce similar result.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Another study found that skill in copying Chinese pseudocharacters was highly correlated with reading scores in children, even with phonological processing skills statistically controlled [Tan et al, 2005b]. A study of Chinese dyslexic children also found that writing and reading are highly correlated [Chan et al, 2006].…”
Section: Introductionmentioning
confidence: 99%